2012
DOI: 10.3892/ol.2012.856
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of Endostar combined with radiation against human nasopharyngeal carcinoma in mouse xenograft models

Abstract: Abstract. Radiation treatment for nasopharyngeal carcinoma (NPC) is common and effective. However, local recurrence occurs frequently. Endostar, a novel recombinant human endostatin, is an antiangiogenic drug with a potent antitumor effect. The present study aimed to observe and explore the radiosensitization effects of Endostar on NPC and its underlying mechanism. The NPC subcutaneous transplantation tumor animal model was established to evaluate the antitumor activity of Endostar combined with radiation (End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…Therefore, radiotherapy combined with anti-VEGF therapy may effectively decrease radiation resistance. 22 Our study also showed no significant association between LRFS and VEGF –460T/C polymorphism. This finding mainly stems from the following factors: first, despite more than 80% of the patients being at the T3–4 stage, the application of IMRT and combined CRT greatly improved the local control of the patients, resulting in 3-year LRFS of more than 90%.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, radiotherapy combined with anti-VEGF therapy may effectively decrease radiation resistance. 22 Our study also showed no significant association between LRFS and VEGF –460T/C polymorphism. This finding mainly stems from the following factors: first, despite more than 80% of the patients being at the T3–4 stage, the application of IMRT and combined CRT greatly improved the local control of the patients, resulting in 3-year LRFS of more than 90%.…”
Section: Discussioncontrasting
confidence: 55%
“…Endostar, a novel modified recombinant human endostatin, has showed strong antiangiogenic effect on various xenograft tumor model and cancer patients, including NPC. [32][33][34] The results of this study demonstrated that Endostar impeded tumor growth without evident tumor regression and that a significant tumor growth inhibition was not observed until day 8, because Endostar was principally cytostatic rather than cytotoxic. It was also shown that Endostar could reduce the tumor vessels, resulting in the decrease of microvessel density, and subsequently lowered the integrin avβ3 expression.…”
Section: Discussionmentioning
confidence: 77%
“…Cells in the early log phase were trypsinized and plated in a 96-well plate at a density of 1x10 4 cells per well. Twenty-four hours later, the medium was removed and replaced with fresh medium with metformin at the indicated concentrations (0, 4,8,16,25,32, 50 and 64 mM) for 24 or 48 h in the presence of 1% fBS. Cell density was measured using the CCK-8 (Dojindo Molecular Technologies, Japan) assay following the manufacturer's instructions.…”
Section: Metformin Inhibits the Growth Of Nasopharyngeal Carcinoma Cementioning
confidence: 99%